The Effect of Two Weeks Physiotherapy on Lower Limb Function and Pain after Lower Limb Amputation - Tadas Pundinas; Saulė Sipavičienė (Lithuanian Sports University, 2019)
Research background. Rehabilitation after amputation is very important, during which the patient receives help, and preparation for prosthetics is underway. During the prosthetic rehabilitation phase, the patient is adapted to use and control the prosthesis. Therefore it is relevant to determine the effect of physiotherapy on limb function and pain. The aim. The aim of the research was to evaluate the effect of two weeks' physiotherapy on lower limb function and pain after lower limb amputation. Methods. The criteria for selection of patients were the primary stage of rehabilitation after lower limb amputation, age more than 18 years. Patients were evaluated before and after the rehabilitation. The evaluated parameters were pain, using visual pain scale (score), muscle strength of the amputated limb using Lovett score system, the range of motion of the joint above the amputated region using a goniometer, functional independence of patients using the functional independence test and in order to fnd out how the patient feels, the self-assessment scale was applied. Results. After the research, limb pain decreased, muscle strength and range of motion improved. The results were statistically signifcant (p < 0.05). Conclusion. After two weeks of physiotherapy, the muscle strength of the amputated limb and the range of motion of the joint movement increased, pain was reduced. Keywords: limb amputation, pain, function, strength, amplitudes.